Beneficial effects of 1-propylphosphonic acid cyclic anhydride as an electrolyte additive on the electrochemical properties of LiNi0.5Mn1.5O4 cathode material - Yan, Guochun; Li, Xinhai; Wang, Zhixing; Guo, Huajun; Xiong, Xunhui (Journal of power sources, 2014)
Self-discharge and transition metal dissolution weaknesses bother the application of LiNi0.5Mn1.5O4 cathode material due to the severe oxidation of electrolyte at the high voltage state. A novel additive, 1-propylphosphonic acid cyclic anhydride (PACA), is desirable to prevent this oxidation. CV and charge–discharge results reveal that adding 0.5% PACA can relieve the oxidation of electrolyte. Consequently, the self-discharge and transition metal dissolution are both suppressed effectively, which is validated by self-discharge tests, XPS, and EDX analyses. Moreover, using PACA as an additive enhances the capacity retention capability of LiNi0.5Mn1.5O4 at elevated temperatures significantly. •1-Propylphosphonic acid cyclic anhydride (PACA) is investigated as an additive.•Self-discharge of LiNi0.5Mn1.5O4 is effectively suppressed by adding PACA into electrolyte.•Enhanced cycling performance of LiNi0.5Mn1.5O4 at elevated temperatures is achieved.•Reduced transition metal dissolution of LiNi0.5Mn1.5O4 by using PACA.